Electronic transport in epitaxial 4H–SiC based Schottky diodes modified selectively by swift heavy ions. (15th August 2020) - Kumar, Vibhor; Maan, A.S.; Akhtar, Jamil
Abstract: Modifications in the defects and electronic transport properties of epitaxial 4H-nSiC(0001) Schottky barrier diodes have been carried out by selective 200 MeV Ag +14 ions irradiation, i.e., ions projected only on the Schottky contact area of the diode using a mask. Forward bias current-voltage (I–V) characteristics are measured in temperature (T) range from 273 K to 473 K. Interestingly, the barrier height found increased from 1.20 eV to 1.35 eV at 273 K and from 1.24 eV to 1.42 eV at 348 K after selective ion irradiation. At T ≥ 373 K, double barrier height features have seen in the I–V-T plots. The reverse bias I–V characteristics are measured up to −200 V, and in T range from 298 K to 473 K. The leakage current density found decreased from 9.57 × 10 -9 A/cm 2 to 2.98 × 10 -10 A/cm 2 at 298 K and from 5.53 × 10 -8 A/cm 2 to 4.17 × 10 -8 A/cm 2 at 373 K after selective irradiation, and deteriorated after that. The defects in pristine SiC with activation energy ( Δ E A ) of 0.29 eV and 0.13 eV are removed and a single defect with Δ E A of 0.38 eV observed after selective ion irradiation. Moreover, asymmetries are observed in capacitance-voltage characteristics of selectively irradiated devices. Role of electronic and nuclear energy loss mechanisms have been discussed to rationalize the performance of diodes. The proposed technique may be applicable in addressing the issues related to interface and bulk level defects in advance semiconducting materials, without using high temperatures.